Whistleblowing System: Do seniors blow less? - Rida Perwita Sari; Lidya Primta Surbakti; Rika Puspita Sari; Dian Anita Nuswantara (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2023)
To fortify itself against any harmful behavior, an organization has meticulously designed a whistleblowing policy system. Despite the availability of this channel, not all members actively engage in using it to contribute to the overall health of the organization. To address this issue effectively, organizations need to conduct in-depth analyses to identify the specific barriers within their context. Our study responds to such topical issues by observing the role of seniority in motivating organizational members to actively embrace their roles as whistle-blowers. The research specifically examines the role of maturity in influencing individuals to step forward and report wrongdoing within the organization. In doing so, we employed the moderated regressions as a methodological approach, involving 396 employees from eight East Java offices of the Directorate General of Taxation. The study's findings provide empirical support for the notion that positive attitudes toward the use of the whistleblowing system significantly increase members' intention to report instances of wrongdoing. However, the research fails to corroborate the hypothesis that age plays a significant role in influencing people’s intention to be whistle-blowers. Considering these results, the implications for organizational governance and policymaking are discussed.